A fresh look at Islam in a multi-faith world : a philosophy for success through education - Wilkinson, M.L.N. (Matthew L.N.) (London ; New York : Routledge, 2015)
'A Fresh Look at Islam in a Multi-Faith World provides a comprehensively theorised and practical approach to thinking systematically and deeply about Islam and Muslims in a multi-faith world. It makes the case for a contemporary educational philosophy to help young Muslims surmount the challenges of post-modernity and to transcend the hiatuses and obstacles that they face in their interaction and relationships with non-Muslims and visa-versa.It argues that the philosophy of critical realism in its original, dialectical and metaReal moments so fittingly'underlabours' (Bhaskar, 1975) for the contemporary interpretation, clarification and conceptual deepening of Islamic doctrine, practice and education as to suggest a distinctive branch of critical realist philosophy, specifically suited for this purpose. This approach is called Islamic Critical Realism.The book proceeds to explain how this Islamic Critical Realist approach can serve the interpretation of the consensual elements of Islamic doctrine, such as the six elements of Islamic belief and the five'pillars' of Islamic practice, so that these essential features of the Muslim way of life can help Muslim young people to contribute positively to life in multi-faith liberal democracies in a globalising world.Finally, the book shows how this Islamic Critical Realist approach can be brought to bear in humanities classrooms by history, religious education and citizenship teachers to help Muslim young people engage informatively and transformatively with themselves and others in multi-faith contexts.'--
'A Fresh Look at Islam in a Multi-Faith World: A Philosophy for Success through Education provides a comprehensively theorised and practical approach to thinking systematically and deeply about Islam and Muslims in a multi-faith world. It makes the case for a contemporary educational philosophy to help young Muslims surmount the challenges of post-modernity and to transcend the hiatuses and obstacles that they face in their interaction and relationships with non-Muslims and visa-versa. It argues that the philosophy of critical realism in its original, dialectical and metaReal moments so fittingly'underlabours' (Bhaskar, 1975) for the contemporary interpretation, clarification and conceptual deepening of Islamic doctrine, practice and education as to suggest a distinctive branch of critical realist philosophy, specifically suited for this purpose. This approach is called Islamic Critical Realism. The book proceeds to explain how this Islamic Critical Realist approach can serve the interpretation of the consensual elements of Islamic doctrine, such as the six elements of Islamic belief and the five'pillars' of Islamic practice, so that these essential features of the Muslim way of life can help Muslim young people to contribute positively to life in multi-faith liberal democracies in a globalising world'--
Includes bibliographical references (page 256-269) and index.
Keywords: Islam; Critical realism; Education -- Philosophy; Islam -- Relations